Desain, Jenis, dan Metode Dalam Penelitian Kualitatif - Andina Aprilia Prawanti; Intan Kumala; Munadiya Nur Fadillah; Rani Yolanda Syahputri Damanik; Reza Noprial Lubis (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
Qualitative research is an approach to understanding human phenomena, culture, and social processes based on the perspective of the subjects studied, so that it can provide deeper meaning to the problems that occur. The design, type, and methods applied are adjusted to the objectives and characteristics of the problem, including ethnography, case studies, document studies, natural observations, phenomenology, grounded theory, historical studies, and biographies, with data collection through interviews, observations, and documentation. Data analysis focuses more on interpretive and inductive processes, so that it is able to explore the relationships and meanings behind the data, and is useful for more mature decision making and policy formulation.